REDUCING TRABILITY BEHAVIOR OF STUDENTS AT MADRASAH DINIYAH ANNUQAYAH LATEE I WITH SELF-MANAGEMENT COUNSELING - Mumayyizah, Fashatul; Nuzulul Khair (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study aims to elaborate on the handling of self-management counseling in overcoming the truancy behavior of students in Latee 1 Annuqayah Guluk-Guluk Sumenep Islamic Boarding School. This research uses a type of quantitative experimental research with a true-experimental design using a pretest-posttest control group design. The research subjects were 10 people who were divided into two groups, namely 5 people in the experimental group and 5 people in the control group. Data collection was carried out using research instruments in the form of a Likert scale and a self-management counseling module. The results obtained in the research show that self-management counseling is effective in overcoming the correct behavior of Madarasah Diniyah Annuqayah Latee I students. This can be proven through the results of the t-test. In the peer-reviewed sample, test the results of the sig value. (2-tailed) was 0.000 < 0.05, while in the independent sample t-test it was 0.001 < 0.05. So it can be concluded that the results of the two tests show that H1 is accepted and H0 is rejected.